Review of the prescription of domiciliary long term oxygen therapy in Scotland. - Morrison, D. (1995)
BACKGROUND--Since 1989 long term oxygen therapy (LTOT) in Scotland has been prescribable only by respiratory physicians, whereas in England and Wales general practitioners can also prescribe this treatment. The effect of this policy has been audited. METHOD--Six hundred and thirty patients were prescribed LTOT in Scotland between 1 October 1989 and 30 September 1991, of which 519 case notes were reviewed. RESULTS--In 79% of patients the diagnosis was chronic obstructive pulmonary disease (COPD), with a near equal male to female ratio. The mean (SD) age was 65 (13) years (range 0.2-90). Sixty percent of patients died during the study period. Compliance with treatment was 14.9 (6.0) hours daily (range 1-24) and in 44% was less than 15 hours daily. Sixty one percent were clinically unstable when assessed and 14% were still smoking. Only 14% of those with COPD fulfilled all of the relative criteria for the prescription of LTOT. Only 56% had a repeated arterial blood gas measurement within 12 months of prescription and 51% of these were taken during a period of clinical instability. Expenditure on oxygen cylinders was six times greater than on oxygen concentrators over this period. CONCLUSIONS--Compliance with LTOT in Scotland, where prescription is the responsibility of respiratory physicians, is similar to other studies and ranges widely. The greatest problem concerning adherence to the guidelines is assessment during clinical instability. The number of deaths suggest that prescription occurs late in the course of the disease. This study highlights the areas where the prescription of LTOT needs to be improved.